Surface tension of model tissues during malignant transformation and epithelial–mesenchymal transition - Nagle, Irène; Richert, Alain; Quinteros, Michael; Janel, Sébastien; Buysschaert, Edgar; Luciani, Nathalie; Debost, Henry; Thevenet, Véronique; Wilhelm, Claire; Prunier, Céline; Lafont, Frank; Padilla-Benavides, Teresita; et al. (Frontiers in Cell and Developmental Biology, 2022)
Epithelial-mesenchymal transition is central to the metastasis process. During this transition, individual cells experience important modifications in terms of division, adhesion, migration and invasion. The translation at the tissue scale of these changes has not yet been enlightened while being essential in the understanding of tumor progression. Biophysical tools dedicated to measurements on model tumor systems are thus needed to reveal the impact of epithelial-mesenchymal transition at the collective cell scale. Herein, using an original biophysical approach based on magnetic nanoparticles insertion inside cells, we form and flatten multicellular aggregates to explore consequences of the loss of the metastasis suppressor NME1 on the mechanical properties at the tissue scale. Multicellular spheroids behave as viscoelastic fluids, their equilibrium shape is driven by surface tension as measured by their deformation upon magnetic field application. In a model of breast tumor cells genetically modified for NME1, we correlate tumor invasion, migration and adhesion modifications with shape maintenance properties by measuring surface tension and exploring both invasive and migratory potential as well as adhesion characteristics